Analysis of thermo-hydrologic-mechanical impact of repository for high-level radioactive waste in clay host formation: An Indian reference disposal system - Dutt A.; Saini M.S.; Singh T.N.; Verma A.K.; Bajpai R.K. (My University, 2025)
In our study, a coupled hydrologic-mechanical analysis is done of the excavation damaged zone, before the emplacement of nuclear waste. This is followed by a coupled thermal-hydrologic-mechanical analysis to evaluate the impact of nuclear waste repository in porous water containing rock mass. This analysis has been under taken in accordance with the Indian reference disposal system. The paper considers the changes in pore pressure and stresses due to excavation of disposal holes. A critical study of rock mass permeability, porosity, thermally induced stresses, strains, and temperature distribution after the emplacement of nuclear spent fuels in disposal holes has also been done. Coupling to the mechanical constitutive equations is done via "effective" normal strain rates. © 2011 Springer-Verlag.